A convenient one-pot synthesis of N-substituted 2-aminoazole derivatives - Sirilata Yotphan (2018)
A practical protocol for the one-pot synthesis of N-substituted 2-aminoazole derivatives is described, employing simple azole substrates, nitrogen nucleophiles, lithium tert-butoxide as the base, and iodine to mediate carbon-nitrogen bond formation. This method proceeds at room temperature under an air atmosphere using a normal benchtop set-up, or can be performed conveniently using microwave irradiation. © Georg Thieme Verlag Stuttgart - New York.